Blushing during social interactions in people with a fear of blushing. - Drummond, P; Back, K; Harrison, J; Helgadottir, F; Lange, B; Lee, C; Leavy, K; Novatscou, C; Orner, A; Pham, H; Prance, J; Radford, D; et al. (2007)
Changes in facial blood flow were investigated during an introductory conversation, delivering a speech, and listening to the speech afterwards in 16 people with a fear of blushing and 16 controls. It was hypothesized that fear of blushing would be associated with high ratings of self-reported blushing intensity and embarrassment during the tasks, and with persistence of the blushing reaction between tasks. Embarrassment and self-reported blushing intensity were greater in the fear-of-blushing group than in controls throughout the experiment. Increases in facial blood flow were similar in the two groups during each of the tasks. However, blushing dissipated more slowly after each task in the fear-of-blushing group than in controls, resulting in an incremental increase in facial blood flow over the course of the experiment. The slow recovery after an episode of blushing might result in physiological or social cues that help to maintain a fear of blushing.